Unproductive school choice debates: all sides assert much that is wrong, misleading, or irrelevant - Merrifield, John D. (Nomos Verlagsgesellschaft mbH & Co. KG, 2023)
The book explains why we desperately need an “Open Education Industry.” It clearly defines the term, and the confusion about what can/should be done to improve schooling outcomes, and why over 30 years of efforts to improve schooling outcomes has left all 51 US school systems far short of what is needed to engage all schoolchildren in high value instruction. Because of past education failures, especially poor basic literacy in economic systems, many influential academics and activists have asserted the presence of adequate market forces where key elements of high-performing markets are absent, and have become pre-occupied with discussion of, and development of, devastating inappropriate generalizations about findings from studies of narrowly-targeted, restriction-laden expansions of access to alternatives to traditional public schools. The book compares those to transformational school choice expansions, and describes key steps towards the inertia that threatens the future or America as a prosperous and free republic.